2014
DOI: 10.1016/j.ajhg.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Integrative DNA, RNA, and Protein Evidence Connects TREML4 to Coronary Artery Calcification

Abstract: Coronary artery calcification (CAC) is a heritable and definitive morphologic marker of atherosclerosis that strongly predicts risk for future cardiovascular events. To search for genes involved in CAC, we used an integrative transcriptomic, genomic, and protein expression strategy by using next-generation DNA sequencing in the discovery phase with follow-up studies using traditional molecular biology and histopathology techniques. RNA sequencing of peripheral blood from a discovery set of CAC cases and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…It has been reported that CD68-positive cells (macrophages or monocytes) predominantly exist at sites of intimal calcification in the coronary artery in patients with chronic kidney disease (13). Moreover, a recent report demonstrated that TREML4, a gene found to be positively associated with coronary artery calcification in cohort studies, is localized in macrophages surrounding the coronary plaques complicated by calcification (14). These observations suggest that macrophages may have played an important role in the onset of peri-strut calcification after SES implantation in the present case.…”
Section: Discussionsupporting
confidence: 64%
“…It has been reported that CD68-positive cells (macrophages or monocytes) predominantly exist at sites of intimal calcification in the coronary artery in patients with chronic kidney disease (13). Moreover, a recent report demonstrated that TREML4, a gene found to be positively associated with coronary artery calcification in cohort studies, is localized in macrophages surrounding the coronary plaques complicated by calcification (14). These observations suggest that macrophages may have played an important role in the onset of peri-strut calcification after SES implantation in the present case.…”
Section: Discussionsupporting
confidence: 64%
“…The models we developed in this study aimed at predicting the binary case-control statuses of Caucasian male patients. Hence, we first transformed the CAC scores (measured by Agatston method (Agatston et al, 1990)) of the 32 Caucasian male subjects from the ClinSeq® study that formed our discovery cohort (data previously published in (Sen et al, 2014a, b)) into binary CAC states. 16 control subjects in this cohort had zero CAC scores corresponding to state “0”, whereas the 16 age-matching cases had high CAC scores (ranging between 500 and 4400) corresponding to state “1”.…”
Section: Methodsmentioning
confidence: 99%
“…Our study focused on Caucasian males due to higher coronary calcium scores observed among men compared to women (Raggi et al, 2008; Maas and Appelman, 2010), as well as higher prevalence of coronary calciumamong white Americans compared to black Americans (Lee et al, 2003). Using random forest modeling, which is a decision tree based machine learning method (Breiman, 2001) established as an effective tool for addressing the complexity of modelling with genomic data (Sun, 2009; Yang et al, 2010b; Dietterich, 2000), we first tested the collective ability of a set of SNPs derived from previous GWAS on CAC (SNP Set-1) in predicting advanced CAC with data from the ClinSeq® study (Biesecker et al, 2009) previously published in (Sen et al, 2014b,a). Upon deriving an alternative SNP set (SNP Set-2) and comparing its predictive ability to SNP Set-1 within the ClinSeq® discovery cohort with and without clinical data, we used data from the Framingham Heart Study (FHS) to test whether we could replicate the observed predictive patterns.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in vivo studies of specific cardiac and vascular cells/ tissues will benefit from improvements in RNA-Seq methodology that will enable extraction and sequencing of RNA from limited numbers of cells/tissues that are difficult to process [26]. RNA-Seq in left ventricular myocardial tissue has been used to systematically identify the disease status of heart failure patients using a limited training dataset of six individuals, including three controls, one ischemic heart disease (ISCH), and two dilated cardiomyopathy (DCM) patients and has been successfully applied to a much larger set of 313 individuals [27].…”
Section: Application Of Transcriptomics To Cad Mechanismsmentioning
confidence: 99%